Current and innovative therapeutic strategies for the treatment of giant cell arteritis. (4th May 2021) - Sebastian, Alwin; Tomelleri, Alessandro; Dasgupta, Bhaskar
ABSTRACT: Introduction : Glucocorticoids represent a highly effective treatment for giant cell arteritis (GCA); however, steroid-dependency frequently hinders an adequate dose reduction. This has led to a flourishing interest in new therapeutic strategies. Areas covered : An analysis of the treatments for GCA was conducted and structured in four sections: summary data supporting the use of glucocorticoids; uncertainty regarding the use of antithrombotic agents are discussed; studies on different conventional steroid-sparing agents are reported; controlled trials with already available biologic agents and the design of those still ongoing are presented. The basis for this review is a literature search on PubMed of studies published until 31 st  December 2020 on GCA treatment. Expert opinion : New GCA patients should be stratified, and therapeutic management should be tailored accordingly. High-risk patients should be treated early with steroid-sparing agents. However, current evidence only supports the use of tocilizumab, with conflicting data on methotrexate. Results of controlled trials evaluating other agents, like mavrilimumab, will be released soon; hopefully, this will lead to their inclusion as alternatives to tocilizumab. Even if biologic drugs seem highly effective, their use could be limited by high costs; hence, clinical research should not forget about less expensive conventional agents, such as leflunomide.